Influence of Water Concentration on the Water/Vapor/ Oil Separation Process in a Vacuum Oil Filter: Modelling and Simulation - Bin, Chen; Ge, Liu (Acta Scientiarum. Technology, 2024)
The vacuum oil filter (VOF) is widely applied in the oil-water emulsion demulsification separation due to the phase separation by using vacuum evaporation; however, the micro-dynamic characteristics of oil, water and vapor three phases and the influencing factors of separation efficiency are rarely studied. Therefore, the fluid flow and phase separation characteristics of water-in-oil emulsions were numerically analysed by ANSYS software. The demulsification conditions of water/oil emulsion were simulated by using the two-fluid model and the water evaporation model, and the turbulence effect was considered by using the Reynolds stress model. The results show that the established model could provide a convenient way to study the effects of the different water concentrations in oil; the turbulence intensity in VOF increases with the increase of water concentration in oil; The separation efficiency has been influenced by the inlet water concentration reaching values between 20.65-22.62% in the center axis, while 33.18-42.24% in the plate column; the vapor concentration ranged from 0 - 23.64% in the center axis, while 0 - 41.02% in the plate column. The relative volume fraction of water concentration decay tending with the water concentration increases, and the water concentration has a great influence on the separation efficiency.